Foolproof sketching & painting techniques for beginners - Kuramae, Tomoko (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2023)
"Packed with practical tips and advice, this book shows you how to fill your sketchbook or watercolor pad with a variety of everyday items that catch your eye. Author Tomoko Kuramae provides detailed step-by-step instructions on sketching and perspective, then shows you how to bring your finished sketches to life with brilliant transparent watercolors. She explains how to draw dozens of objects realistically from a variety of angles based on cubes and cylinders"--Page 4 of cover.